Lifestyle intervention Tai Chi for adult patients with type 2 diabetes mellitus: a PRIO-harms based overview of 17 systematic reviews - Zhang, Furong; Chen, Xixi; Liu, Xicen; Shen, Xiaoyu; Liu, Tianyu; Zeng, Fang; Jin, Rongjiang (Frontiers in Endocrinology, 2024)
Objective: To systematically summarize current evidence and determine the clinical effectiveness and safety of Tai Chi for type 2 diabetes mellitus(T2DM) in adults by conducting an overview of systematic reviews(SRs).Methods: A systematic search encompassing five electronic databases was conducted until July 30, 2023, to identify relevant systematic reviews (SRs) based on randomized controlled trials (RCTs) concerning Tai Chi for T2DM. The methodological quality of the included SRs was assessed using the A MeaSurement Tool to Assess systematic Reviews (AMSTAR 2) and the Risk of Bias in Systematic Reviews (ROBIS) tool. The Preferred Reporting Items for Overview of Systematic Review (PRIO-harms) checklist was used to promote a more balanced reporting of benefits and harms in this overview. Corrected covered area(CCA) was used to calculate the degree of overlapping primary studies. Primary outcome measures were glycosylated hemoglobin (HbA1c) and fasting blood glucose (FBG), while secondary outcomes encompassed health-related quality measures. The GRADE (Grades of Recommendations, Assessment, Development, and Evaluation) framework was utilized to assess the quality of evidence for outcome measures.Results: A total of 17 eligible SRs were included in this overview. One SR reported negative conclusions while the remaining 16 reported positive ones on different outcomes. Four SRs reported adverse events, either absent or minor. Most of SRs exhibited critically low quality (15/17) and a high risk of bias(14/17), as indicated by AMSTAR2 and ROBIS, respectively. The CCA was 12.14%, indicating a high degree of primary study overlapping. Evidences from 135results concerning 24 outcomes concerning Tai Chi for T2DM were evaluated by GRADE approach, most of which were rated very low.Tai Chi shows promise as a potentially effective and safe lifestyle intervention for adults with T2DM, particularly on improving HbA1c, FBG, BMI, and overall quality of life (QoL). However, these results should be cautiously interpretated due to methodological flaws observed in the current SRs and low quality based on GRADE. Furthermore, there is a compelling need for additional well-designed, highquality RCTs and SRs to establish robust and conclusive evidence regarding the efficacy of Tai Chi for managing T2DM in the future.